TRANSFORMASI DIGITAL UMKM MELALUI APLIKASI JOKER (JASA ORDER KETIKA MAGER) - Liza Trisnawati; Salamun Salamun; Muhammad Roby (LPPM Universitas Abdurrab, 2025)
Technological progress demands that all human work which in daily life still uses manual methods and whose performance is deemed less effective can be done with advanced technology. The food ordering process is generally carried out directly and via media such as WhatsApp, where customers contact restaurant staff regarding the available menu, the price of each food, the delivery process and payment. This ordering process takes more time, so the ordering process becomes less effective, because the officer has to reply to messages one by one to each customer regarding price, available stock, and delivery process. Therefore, creating ordering media in the form of an application can be a solution to overcome deficiencies and be able to mediate both the ordering process and product delivery. Data collection took the form of literature studies, interviews and observations. Quantitative methods are used in this research process to be used in conducting testing. The joker application was tested using black box testing successfully and a User Acceptance Test (UAT) was carried out by obtaining an average score of 92.48% from 1,000 customer orders with the title